Endogenous anabolic hormone responses to endurance versus resistance exercise and training in women - Consitt, L. A.; Copeland, J. L.; Tremblay, M. S. (Sports Medicine, 2002)
Research in exercise endocrinology has flourished over the past few decades. In general, research examining short- and long-term hormone responses to endurance exercise preceded studies on resistance exercise, and research on women lagged behind research on men. Sufficient data are now available to allow a comparison of endogenous anabolic hormone responses to endurance versus resistance exercise and training in women. Circulating levels of testosterone, dehydroepiandrosterone, dehydroepiandrosterone sulphate, estradiol, growth hormone and cortisol have been shown to increase in response to an acute bout of endurance exercise in women. However, only growth hormone, estradiol and cortisol have been reported to increase following resistance exercise. Hormone changes following training, either endurance or resistance, have been variable, probably because of differences in experimental design and major differences in the length, intensity and volume of training programmes. With the notable exception of growth hormone, the anabolic hormones reviewed here appear to decline with endurance training. Resistance training has little effect on resting hormone levels, except insulin-like growth factor-I, which has been shown to increase following a training programme. These hormone changes potentially have both metabolic and hypertrophic implications, and future research needs to focus on the biological significance of these adaptations.